A case of post‐COVID‐19 myalgic encephalomyelitis/chronic fatigue syndrome characterized by post‐exertional malaise and low serum acylcarnitine level. Issue 2 (10th February 2023) - Jinushi, Ryuhei; Nishiguchi, Sho; Masuda, Sakue; Sasaki, Akiko; Koizumi, Kazuya; Ryozawa, Shomei
Abstract: COVID‐19 afflicts patients with acute symptoms and longer term sequelae. One of the sequelae is myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), which is often difficult to diagnose, having no established tests. In this article, we synthesize information from literature reviews on patients with ME/CFS that developed after recovery from COVID‐19.